Nucleotide excision repair is a potential therapeutic target in multiple myeloma - Szalat, R; Samur, M K; Fulciniti, M; Lopez, M; Nanjappa, P; Cleynen, A; Wen, K; Kumar, S; Perini, T; Calkins, A S; Reznichenko, E; Chauhan, D; et al. (Leukemia, 2018)
Despite the development of novel drugs, alkylating agents remain an important component of therapy in multiple myeloma (MM). DNA repair processes contribute towards sensitivity to alkylating agents and therefore we here evaluate the role of nucleotide excision repair (NER), which is involved in the removal of bulky adducts and DNA crosslinks in MM. We first evaluated NER activity using a novel functional assay and observed a heterogeneous NER efficiency in MM cell lines and patient samples. Using next-generation sequencing data, we identified that expression of the canonical NER gene, excision repair cross-complementation group 3 ( ERCC3 ), significantly impacted the outcome in newly diagnosed MM patients treated with alkylating agents. Next, using small RNA interference, stable knockdown and overexpression, and small-molecule inhibitors targeting xeroderma pigmentosum complementation group B (XPB), the DNA helicase encoded by ERCC3 , we demonstrate that NER inhibition significantly increases sensitivity and overcomes resistance to alkylating agents in MM. Moreover, inhibiting XPB leads to the dual inhibition of NER and transcription and is particularly efficient in myeloma cells. Altogether, we show that NER impacts alkylating agents sensitivity in myeloma cells and identify ERCC3 as a potential therapeutic target in MM.